Multifault complex rupture and afterslip associated with the 2018 Mw 6.4 Hualien earthquake in northeastern Taiwan. Issue 1 (5th October 2020) - Zhao, Dezheng; Qu, Chunyan; Shan, Xinjian; Bürgmann, Roland; Gong, Wenyu; Tung, Hsin; Zhang, Guohong; Song, Xiaogang; Qiao, Xin
SUMMARY: We investigate the coseismic and post-seismic deformation due to the 6 February 2018 M w 6.4 Hualien earthquake to gain improved insights into the fault geometries and complex regional tectonics in this structural transition zone. We generate coseismic deformation fields using ascending and descending Sentinel-1A/B InSAR data and GPS data. Analysis of the aftershocks and InSAR measurements reveal complex multifault rupture during this event. We compare two fault model joint inversions of SAR, GPS and teleseismic body waves data to illuminate the involved seismogenic faults, coseismic slip distributions and rupture processes. Our preferred fault model suggests that both well-known active faults, the dominantly left-lateral Milun and Lingding faults, and previously unrecognized oblique-reverse west-dipping and north-dipping detachment faults, ruptured during this event. The maximum slip of ∼1.6 m occurred on the Milun fault at a depth of ∼2–5 km. We compute post-seismic displacement time series using the persistent scatterer method. The post-seismic range-change fields reveal large surface displacements mainly in the near-field of the Milun fault. Kinematic inversions constrained by cumulative InSAR displacements along two tracks indicate that the afterslip occurred on the Milun and Lingding faults and the west-dipping fault just to the east. The maximum cumulative afterslip of 0.4–0.6 m occurred along the Milun fault within ∼7 months of the main shock. The main shock-induced static Coulomb stress changes may have played an important role in driving the afterslip adjacent to coseismic high-slip zones on the Milun, Lingding and west-dipping faults.